2009
DOI: 10.1097/ico.0b013e31818d3aef
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications After Primary Adult Optical Penetrating Keratoplasty: Prevalence and Impact on Graft Survival

Abstract: The prevalence of post-PKP complications and their impact on graft survival vary significantly among surgical indications for primary adult optical PKP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 79 publications
3
39
0
2
Order By: Relevance
“…For nearly half a century, penetrating keratoplasty (PKP) has been the surgical treatment of choice for visual rehabilitation of keratoconus (KC) [1][2][3][4][5][6][7][8][9]. Recently, deep anterior lamellar keratoplasty (DALK) has been introduced as an alternative to PKP.…”
Section: Introductionmentioning
confidence: 99%
“…For nearly half a century, penetrating keratoplasty (PKP) has been the surgical treatment of choice for visual rehabilitation of keratoconus (KC) [1][2][3][4][5][6][7][8][9]. Recently, deep anterior lamellar keratoplasty (DALK) has been introduced as an alternative to PKP.…”
Section: Introductionmentioning
confidence: 99%
“…The results further extend the outcome of previous studies that reported the occurrence of one or more complications is associated with an increased risk of graft failure, whereas specific types of complications were not related to risk for graft failure. 24 Some of the complications noted in the present study could be considered less severe than others, such as Desçement's folds and endothelial pigmentation. Excluding these from the overall complications did not affect substantially the results of the analyses.…”
Section: Discussionmentioning
confidence: 89%
“…However, one of the most common causes of rejection is associated with endothelial failure surgical technique, which represents a substantial risk to the probability of graft survival, especially if not recognized and treated in time [4,5].…”
Section: Introductionmentioning
confidence: 99%